Architectural Breakdown of End-to-End Latency in a TCP/IP Network - Larsen, Steen; Sarangam, Parthasarathy; Huggahalli, Ram (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2007)
Adoption of the 10 GbE Ethernet standard has been impeded by two important performance-oriented considerations: 1) processing requirements of common protocol stacks and 2) end-to-end latency. The overheads of typical software based protocol stacks on CPU utilization and throughput have been well evaluated in several studies. In this paper, we focus on end-to-end latency and present a detailed characterization across typical server system hardware and software stack components. We demonstrate that application level end-to-end latency with a 10 GbE connection can be as low as 10 microseconds for a single isolated request. The paper analyzes the components of the latency and discusses possible significant variations to the components under realistic conditions. We note that methods that are used to optimize throughput can often be responsible for the perception that Ethernet based latencies can be very high. Methods to pursue reducing the minimum latency and controlling the variations are presented.